Imidazole-containing triblock copolymers with a synergy of ether and imidazolium sites1. Issue 16 (28th April 2015) - Jangu, Chainika; Wang, Jing-Han Helen; Wang, Dong; Fahs, Gregory; Heflin, James R.; Moore, Robert B.; Colby, Ralph H.; Long, Timothy E.
<x xml:space="preserve">Abstract</x> Reversible addition–fragmentation chain transfer (RAFT) polymerization enabled the synthesis of well-defined A–BC–A triblock copolymers containing a synergy of pendant ether and imidazolium sites.